2017
DOI: 10.3892/mmr.2017.6322
|View full text |Cite
|
Sign up to set email alerts
|

Mice endometrium receptivity in early pregnancy is impaired by maternal hyperinsulinemia

Abstract: Previous studies have investigated the lower embryo implantation rates in women with polycystic ovary syndrome, obesity and type 2 diabetes, and specifically the association between the abnormal oocyte and embryo and hyperinsulinemia. The importance of hyperinsulinemia on maternal endometrium receptivity remains to be elucidated. The present study used a hyperinsulinemic mouse model to determine whether hyperinsulinemia may affect endometrial receptivity. An insulin intervention mouse model was first establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…However, little has been reported on the regulatory effects of high-level insulin on the endometrium. Our previous study found that high levels of insulin could result in impaired endometrial receptivity and further affect endometrial decidualization in early pregnant mice (Li et al 2017).…”
Section: Introductionmentioning
confidence: 98%
“…However, little has been reported on the regulatory effects of high-level insulin on the endometrium. Our previous study found that high levels of insulin could result in impaired endometrial receptivity and further affect endometrial decidualization in early pregnant mice (Li et al 2017).…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, in humans more than half of all embryos may fail to implant or abort soon after implantation (Wilcox et al, 1999). This number can be substantially higher under maternal adversity (Bellver et al, 2013;Dechanet et al, 2011;Li et al, 2017b). We therefore expect that maternal adversity could generate intense selection on gene expression and the associated epigenomic profiles, in particular during implantation.…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesized reasons of IR on ART failure in both RIF and RPL were that IR may be related to the decreased oocyte quality [30,31], poor embryonic development [32,33] and decreased endometrial receptivity [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…That may be an important cause of incomplete embryo implantation and miscarriages [40]. IR and hyperinsulinemia may in uence decidualization by multiple factors like prokineticin 1, forkhead-O1 [41], insulin-like growth factor binding protein-1 [42], hox gene A10 [34] and endometrial protein PP14 [43]. A study conducted by Hu et al on pregnant rats demonstrated that insulin resistance induced damage mediated by mitochondria as well as the subsequent imbalance of oxidative stress responses in the gravid uterus [44].…”
Section: Discussionmentioning
confidence: 99%